Grain-boundary diffusion of oxygen in polycrystalline ferrites; Russian Physics Journal; Vol. 42, iss. 5 - Surzhikov A. P. Anatoly Petrovich; Peshev V. V.; Pritulov А. M.; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (1999, 1999)
Title screen